Focus on festivals contemporary European case studies and perspectives - Newbold, Chris (Goodfellow Publishers, 2015)
"This book presents a contemporary overview of our most ubiquitous cultural phenomena - festivals. It is able to do so by taking a powerful and unique case-study focused, theoretically rigorous and pan-European approach. It comes from a hugely expert and experienced team of editors and authors drawn from across Europe and is based on the groundbreaking work of the European Festival Research Project (EFRP). The EFRP and the book are focused on understanding the causes and implications of the current growth in festivals internationally, and the implications this has across major sectors ranging from tourism to culture"--Provided by publisher.